African American Family Disintegration and Terry McMillan - AGUESSY, ANNE NATHALIE JOUVENCIA AGOSSI (My University, 2017)
Customarily, two forms of family have existed: the nuclear family made of a wife, a husband and children or without children, as well as the extended family, which includes all kith and kin. But nowadays, the number of single parent households, mainly maintained by women designated as female heads of family, has been increasing giving way to fatherless families. But I realize that besides that female headed families, there are other groupings of families today: male headed families, cohabiting families, heterosexual families, mixed families, childless families and homosexual families and among them there are some features of dysfunctional families. This situation is quite critical in Black American community and reveals that Black families have been threatened. Since the family is the cell of the society, this paper aims to explore the problematic of family in some Terry McMillan’s fictional works and I will attempt redefining the family. This study draws on Psychoanalytical criticism for theoretical insight and orientation.
Keywords: Psychoanalytical criticism; Black Families; dysfunctional families; Terry McMillan’s fictional works.